Refleksje nad przemijaniem i istotą czasu w codziennym życiu człowieka. Analiza pragmalingwistyczna felietonów Macieja Stuhra = Reflections on the passing of time and the essence of time in everyday human life. Pragmalinguistic analysis of Maciej Stuhr`s columns - Boś, Tina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article contains a pragmalinguistic analysis of lexemes expressing the notion of time present in Maciej Stuhr`s columns. S. Borawski`s quantitative?qualitative method was used to find the most frequent words in the texts. On this basis it was possible to notice the diverse way in which the author perceives time and to classify the lexeme according to three semantic categories: the past, i.e. the autor`s memories, then reflections on the passing of time and the essence of time in everyday human life, and the future, i.e. the columnist`s futuristic visions.
Keywords: analiza pragmalingwistyczna; czas; przemijanie; felieton; językowy obraz świata; pragmalinguistic analysis; time; transience; column; linguistic image of the world